Fixed Points of Difference Operator of Meromorphic Functions - Zhaojun Wu; Hongyan Xu (The Scientific World Journal)
Let f be a transcendental meromorphic function of order less than one. The authors prove that the exact difference Δf=fz+1-fz has infinitely many fixed points, if a∈ℂ and ∞ are Borel exceptional values (or Nevanlinna deficiency values) of f. These results extend the related results obtained by Chen and Shon.